ANALISIS PENCAPAIAN SISWA SMP DALAM MENYELESAIKAN SOAL PERSAMAAN LINEAR DUA VARIABEL DI SMPN 1 CAMPAKA MULYA-CIANJUR - Ruslan Mubarok; Nelly Fitriani (IKIP Siliwangi, 2020)
This study aims to analyze the achievement of junior high school students in solving the Two Variable Linear Equation System (SPLDV) questions, this material is one of the materials that junior high school students generally lack in power. The subjects of this study were 25 students of class IX-C at SMPN 1 Campaka Mulya-Cianjur, who then took a sample of 6 people representing high, medium, and low ability students for analysis. The method in conducting this research is a case study. The instrument for obtaining the data itself was carried out by a test given to students in the form of a question sheet containing 3 contextual questions with questions that had different difficulty levels. Based on the research that has been done, it turns out that the mistakes of students in solving SPLDV questions are different. From the test results there were 2 students with high abilities, 2 students with moderate abilities, and 21 students with low abilities